The role of cilostazol, a phosphodiesterase 3 inhibitor, on oocyte maturation and subsequent pregnancy in mice. - Min Li (Public Library of Science (PLoS), 2012)
It is important to identify effective contraceptive drugs that cause minimal disruption to physiological processes. Phosphodiesterase 3 (PDE3) inhibitors suppress meiosis in oocytes by decreasing the level of cAMP and blocking the extrusion of the first polar body. In this study, we tested the PDE3 inhibitor, cilostazol, as a potential contraceptive agent. The effects of cilostazol treatment in vitro and in vivo on the suppression of oocyte maturation in a mouse model were investigated. The results indicated that treatment with increasing concentrations of cilostazol led to a dose-dependent arrest in meiosis progression. The effective in vitro concentration was 1 µM and was 300 mg/kg in vivo. The effect of cilostazol was reversible. After removal of the drug, meiosis resumed and mouse oocytes matured in vitro, and showed normal chromosome alignment and spindle organization. After fertilization using an ICSI method, the oocytes showed normal morphology, fertilization rate, embryo cleavage, blastocyst formation, and number of viable pups when compared with controls. The offspring showed similar body weight and fertility. In vivo, the mice became infertile if the drug was injected sequentially, and became pregnant following discontinuation of cilostazol. More importantly, no side effects of cilostazol were observed in treated female mice as demonstrated by blood pressure and heart rate monitoring. It is concluded that cilostazol, a drug routinely used for intermittent claudication, can effectively inhibit oocyte maturation in vitro and in vivo, does not affect the developmental potential of oocytes following drug removal and has few side effects in female mice treated with this drug. These findings suggest that cilostazol may be a potential new contraceptive agent that may facilitate an efficacy and safety study of this drug.